DATA MINING ASSOSIATION RULE UNTUK MENDUKUNG SISTEM PENCAPAIAN TARGET PAJAK PENDAPATAN DAERAH STUDI KASUS DI KABUPATEN DELI SERDANG - Muhammad Eka; Rara Astili Siregar (STMIK Budi Darma, 2018)
Deli Serdang Regency has a complete and unique topography because there are coastal areas, lowlands and mountainous highlands with an area of 2,497.72 Ha consisting of 22 sub-districts, 380 villages and 14 villages. The main potential of the Deli Serdang regency are agriculture, smallholder plantations, large plantations, fisheries, aquaculture, livestock, industry, trade and tourism. Based on this big potential, Deli Serdang District Region has a large potential income tax. Planning and regional income tax management system of Deli Serdang Regency are carried out at the Regional Revenue Department of Deli Serdang Regency. Based on achievement data of tax revenue which is posted on Regional Deliberation Separtment of Deli Serdang Regency website, rate of regional income is still slow. The target line graph and the realization of regional revenues indicate that the targets have to be achieved are still far, because until June 2017 achievement only Rp. 56,950,403,904.02, - while the target to the end of December 2017 is Rp. 484,520,000,000. To achieve the annual target as expected need a strategy. Association analysis is also known as one of the data mining techniques basis of various other mining data techniques. By using the Apriori Algorithm, an analysis of the obstacles in achieving targets can be done to find interesting rules that are useful in supporting the system of achieving local tax targets. The implementation of Association Rule to support the achievement of the tax target is expected to help the process of achieving the target of regional income tax, especially in the Regional Revenue Department of Deli Serdang Regency.Keywords: Data Mining,Assosiation Rule, Apriori